PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PERATAAN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia) - Imas Gandasari; Vinola Herawaty (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
The purpose of this study was to examine the influence of return on assets, net profit margin, dividend payout ratio, financial leverage and firm age to income smoothing moderated good corporate governance as well as to test the size of the company that will control the income smoothing. This study used logistic regression test. Samples are companies listed on the Jakarta Stock Exchange by taking a sample of 174 firms from 2011-2013. Sampling is done by using purposive sampling method. Test the above hypothesis used SPSS 20. Based on the analysis it can be concluded that the dividend payout ratio negatively affect income smoothing, while the return on assets, net profit margin, financial leverage¸ firm age no significant effect on income smoothing. Good corporate governance can only moderate the effect of the dividend payout ratio to income smoothing. The size of the company as variable controls of an effect on income smoothing.